Variations in Children’s screen time behaviors by weight status among a mostly disadvantaged population - Paul Son; Yuxin Nie; Qiaoyin Tan; Pengfei Yang; Peyton Murray; Amanda E. Staiano; Fahui Wang; Gang Hu; Stewart Gordon; Senlin Chen (PLoS ONE, 2026)
The purpose of this survey study was to comprehensively examine if various types of screen time differed between children with overweight or obesity (OWOB; ≥ 85 th BMI percentile) vs. normal weight (NW: < 85 th BMI percentile) in a largely socioeconomically disadvantaged population. 739 parent proxies of children aged 5–11 years ( M = 9.27, SD = 1.49) mostly enrolled in Medicaid (83.9%) in a United States (US) southern state responded to an online questionnaire called the Movement Behavior Questionnaire – Child (MBQ-C; open version). Eight items of the MBQ-C separately measured passive and interactive screen time on weekdays and weekend days. The survey also gathered parent-reported child weight and height, along with their sociodemographic characteristics. Compared to children with NW ( M = 294.5 ± 7.2 min/day), children with OWOB ( M = 364.3 ± 10.6 min/day) reported greater amount of total screen time ( M Diff = 69.8 min/day, 95% CI = [45.0–94.6], p < 0.001). Of the sample, 24.9% met the sedentary screen time guidelines of no more than 2 hours/day favoring children with NW ( OR = 0.59, 95% CI [0.39, 0.86], p = 0.008). The difference of screen time between weight-status groups was greatest in passive screen time, particularly on weekdays ( M Diff = 63.2 min/day, 95% CI = 47.6–78.7, p < 0.001). Demographic factors did not significantly moderate the relationship between screen time and weight status. Most of the disadvantaged children failed to meet the screen time guidelines. Children with OWOB reported higher screen time, particularly passive screen time on weekdays. These findings suggest the need for tailored interventions to not only curb overall screen time but also mitigate specific types of screen time behaviors on specific days for children with OWOB (i.e., passive screen use on weekdays).